A fórmula desenvolvimento sustentável na mídia mato-grossense - Alcântara, Gleice Antonia Moraes (2011)
Our research aims to analyze the discursive meanings that are given to move around the formula "sustainable development / sustainability" in the journalistic discursive space of Mato Grosso. We took as reference, to the constitution of our corpus, matters of a major newspaper of the State, A Gazeta, located in Cuiabá. As time frame, we established comprising of the years 2006 to 2010. The interest in the issue grew out of reflections as a professor of education which has as one of their roles in the promotion and integration of the content of environmental education in school life, and especially by observing how the environment has been engineered in different ways in various social spaces, through the noun formula " sustainable development / sustainability”. With this in mind, we believe that the school becomes one of the spaces for discussion and awareness to the issue, focusing on denaturing the hegemonic discourse, capitalist, developmental, and ingrained in our society. We hypothesized that in those spaces the hegemonic discourse is predominant. Therefore, we propose highlight these speeches, scrutinizing them to de-naturalise them. Thus we ask: which way they were and are being built on the formula "sustainable development / sustainability" in the media space that we direct our theoretical and analytical sight? What is the role of media in circulation and crystallization of the formula? To answer these questions, we will use the guidelines of the Discourse Analysis of the French line, derived from the propositions of Michel Pêcheux, mobilizing concepts such as memory and discursive event. However, to address more specifically, to think the formula "sustainable development / sustainability," the perspective of discourse, we will seek contributions in Alice Krieg-Planque (2003 and 2007) and also in Guilhaumou (2009), exploring the analytical category of narrative the event to reflect on how this formula builds distinct discursive events.